THE INFLUENCE OF CODE-SWITCHING ON ENGLISH LANGUAGE PROFICIENCY AMONG BILINGUAL UNIVERSITY STUDENTS - Mochammad Asmi Rizaldy; Muhamad Khoerul Hadist (Journal of Innovative and Creativity, 2025)
This study investigates the influence of code-switching on English language proficiency among bilingual university students in Universitas Muhammadiyah Bogor Raya. Employing a mixed-method approach, data were gathered through Likert-scale questionnaires, semi-structured interviews, and classroom observations. The quantitative findings reveal that code-switching is commonly used, especially when students encounter difficulties in expression. The Spearman correlation test shows a significant positive relationship between code-switching function and perceived English proficiency. Furthermore, multiple linear regression indicates that the function of code-switching significantly contributes to language development, while frequency alone does not. Qualitative data support these findings by illustrating how code-switching helps students clarify meaning, build confidence, and adjust to social contexts. The study concludes that code-switching, when used purposefully, can be a supportive tool for bilingual learners in EFL settings.